Fritz Jahr as methodological paradigm in bioethical education - Perušić, Luka (Array, 2019)
The paper examines Fritz Jahr as a possible role-model in bioethical education. It consists of two parts. The first part builds upon the acknowledged data and theories about how Fritz Jahr proposed the bioethical imperative and changed his way of thinking. It provides arguments for and against known claims and expands the knowledge background with the focus on reconstructing the thought process and some presumptions that led to the formulation of bioethical imperative. The second part uses these results to infer five features to show how we can extract and define methodological features from Jahr’s personality and activity, which confirm and enhance integrative projects. An attempt has been made to understand that something, such as “Jahrian methodology”, might be sensible enough to provide scientific knowledge and cultural orientation without simplifying the bios, but that it is pointless without integration with educational models, and to emphasise this I conclusively consider the role of bioethicists in the 21st century.